A Retrospective Study on the First Cerebrospinal Fluid Taken from External Ventricular Drainage Insertion in Meningitis Patients with Hydrocephalus - Afifi, Asma’ Mohamad (Malays J Med Sci, 2019)
BACKGROUND: Ventriculoperitoneal (VP) shunting is a permanent form of cerebrospinal fluid (CSF) diversion that can be performed for hydrocephalus. Sterility of the CSF is an important prerequisite for permanent shunt placement. It has been hypothesised that in early stage of meningitis, ventricular CSF remains sterile. A study is conducted on the first CSF sample taken from patients suspected to have meningitic hydrocephalus. METHOD: A retrospective review case records of patients who had undergone external ventricular drainage (EVD) for suspected meningitic hydropcephalus in Hospital Sultanah Aminah Johor Bahru (HSAJB), Johor, Malaysia. RESULTS: Fifty-one cases were analysed. Mean age of patients was 37.27 years old, with 64.7% of them was male. Univariate analysis revealed that the main parameters to determine CSF sterility were CSF glucose (95% CI, 0.852, 10.290, P = 0.001), CSF protein (CI 95%, 0.722, 14.898, P < 0.001), CSF gram stain (95% CI, 16.437, 0.877, P < 0.001 ) and CSF appearance ( 0.611, 6.362, P = 0.012). Multivariate analysis had proven that gram stain was the main parameter in the CSF analysis (CI 95%, 16.437, 0.029, P = 0.016). No significant differences in CSF results were observed from EVD and lumbar puncture. CONCLUSION: The most significant parameter in CSF to determine infection was gram stain.